Methodological Balance: the Areal Concept of Ivo Pospisil in the Context of Russian Stud - ies of the 20th Century and of Ukrainian Literary Critics Ideas - Tychinina, Alyona (Verbum : Praha, 2022)
Abstract: The article under studies identifes the methodological ties between mod - ern Czech and Ukrainian literary studies on the example of Ivo Pospisil’s monograph „Methodology and Theory of Literary Slavic Studies and Central Europe” (2015). The methodological platform of the scientist is shown in dynamics: comparative studies, phenomenology, historical poetics, genre studies and areal studies. Areal (spatial) phi - lology becomes the methodological framework and „cognitive tool” in the above-men tioned work. Within the specifc features of the hermeneutic circle, I. Pospisil outlines the methodological principles of Brno areal studies, as well as substantiates the powers of areal methodology. Hence, by means of deduction, he narrows the areas of its application and eventually connects spatial poetics to the analysis of specifc texts of modern Czech literature. It is concluded that the „methodological balance” of Czech and Ukrainian literary criticism is ensured by common „pendulum movements” in the history of the literary process, common theoretical and literary basis (to works by O. Potebnya, M. Bakhtin, D. Chyzhevsky, D. Dyurishin), parallel infuences of Western European literary criticism, as well as collective conference events and consensual research optics.
МЕТОДОЛОГИЧЕСКОЕ РАВНОВЕСИЕ: АРЕАЛЬНАЯ КОНЦЕПЦИЯ ИВО ПОСПИШИЛА В КОНТЕКСТЕ РУССИСТИКИ ХХ СТ. И ИДЕЙ УКРАИНСКИХ ЛИТЕРАТУРОВЕДОВ
Keywords: comparative methodology; methodological balance; Brno Literary School; areal philology; areal literary studies; Ivo Pospisil